When Everyone Wins: Dialogue, Play, and Black History for Critical Games Education - Rouse, Rebecca (2022)
In this article, we reflect on the process and outcomes of using dialogue, play, and a focus on Black women’s history to support critical media literacy in game design education. Over three years we developed a dialogue-based introductory undergraduate course in the game design program at Rensselaer Polytechnic Institute intended to deepen engagement by students in game design practice. We specifically focused on critical approaches to explore the history and culture of games, utilizing dialogic pedagogy to develop transformative learning environments rooted in social justice education, and helped students develop skills for intercultural dialogue and communicating “across difference.” The dialogue experience created a powerful learning environment that resulted in higher quality and more critical student game design work. This was evident in the 2019 iteration of the course, which included two sections of students and in which we had a semester-long group project on the history of Harriet Tubman, culminating in a selection of student games being shown at a local gallery in an exhibition celebrating Tubman’s legacy. The Tubman project was liberatory not only for students, but also instructors, as we learned together how to navigate discomfort and gain a more critical understanding of the material realities of white supremacy in games, self, and each other. This article shares details from the design and methodology of our course, outcomes as evidenced by student work, survey responses, and instructor observations, and concludes with reflections on areas for further research and opportunities for other educators to incorporate new methods in design education.